HCV dispersal patterns among intravenous drug users (IDUs) in Athens metropolitan area. - Papachristou, Eleni; Tsagkovits, Aikaterini; Zavitsanou, Assimina; Hatzakis, Angelos; Paraskevis, Dimitrios (Infect Genet Evol, 2016)
BACKGROUND: Most of the HCV transmission the recent years in Greece was among IDUs. Our aim was to estimate the prevalence of HCV genotypes and to investigate the patterns of HCV dispersal among IDUs in Athens using current state of the art molecular epidemiology methods. METHODS: HCV sequences were determined from 238 HIV-negative IDUs collected on the basis of the "ARISTOTLE" prevention program carried out in Athens between 2012 and 2013. Phylogenetic trees were inferred on HCV sequences isolated from IDUs in Athens for the most prevalent HCV clades (subtypes 1a and 3a). Phylogenetic analysis was performed by Neighbor-Joining and Bayesian methods using GTR+G as nucleotide substitution model. HCV dispersal patterns were estimated using as references, all globally available HCV sequences for subtypes 1a and 3a. RESULTS: The prevalence of HCV subtypes was: 3a (59.2%), 1a (21.9%), 4 (13.0%), 1b (5.4%) and 2 (0.5%). Phylogenetic analyses revealed that most sequences (63.5%) οf subtypes 1a and 3a fell within IDU-specific monophyletic groups. The proportion of sequences in monophyletic clades was similar for subtype 3a (62.9%) and 1a (65.3%). For the latter group, monophyletic clades were smaller in size. Multivariable logistic regression analyses showed that monophyletic clustering was marginally associated recent onset of injecting ([AOR]=1.44; 95% CI (0.97-2.13), p=0.068). CONCLUSIONS: The high proportions of HCV sequences within IDU-specific monophyletic clusters suggest that transmissions occurred locally among IDUs in Greece. The numerous clusters for both 1a and 3a provide evidence that both sub-epidemics were the result of multiple introductions among the IDUs. Higher regional clustering was probably associated with a more recent onset of drug use.
Keywords: Adult; Drug Users; Female; Greece; Hepacivirus; Hepatitis C; Humans; Male; molecular epidemiology; Phylogeny; Prevalence; Substance Abuse, Intravenous